Odpowiedzi

2010-01-20T19:07:34+01:00
A) Sn= 1/2n(3n+1)

S1 = 1/2 * 1 * (3+1) = 2
S1 = a1
a1=2

S2 = 1/2 * 2 * (6+1)=7
S2 = S1 + a2 = 2 + a2
2 + a2 = 7
a2 = 5

S3 = 1/2 * 3 * 10 = 15
S3 = S2 + a3 = 7 + a3
7 + a3 = 15
a3 = 8

mamy ciąg: 2, 5, 8, ...
r = 3
an=a1 + (n-1)r
an = 2 + (n-1)3
an = 2 + 3n - 3
an = 3n - 1


b) Sn= n(3n+5)/2

S1 = 1 * 8 : 2 = 4
S1 = a1
a1=4

S2 = 2 * 11 : 2 = 11
S2 = S1 + a2 = 4 + a2
4 + a2 = 11
a2 = 7

S3 = 3 * 14 : 2 = 21
S3 = S2 + a3 = 11 + a3
11 + a3 = 21
a3 = 10

mamy ciąg: 4, 7, 10, ...
r = 3
an=a1 + (n-1)r
an = 4 + (n-1)3
an = 4 + 3n - 3
an = 3n + 1


c) Sn=2n^2-n

S1 = 2 * 1 - 1 = 1
S1 = a1
a1=1

S2 = 2 * 4 - 2 = 6
S2 = S1 + a2 = 1 + a2
1 + a2 = 6
a2 = 5

S3 = 2 * 9 - 3 = 15
S3 = S2 + a3 = 6 + a3
6 + a3 = 15
a3 = 9

mamy ciąg: 1, 5, 9, ...
r = 4
an=a1 + (n-1)r
an = 1 + (n-1)4
an = 1 + 4n - 4
an = 4n - 3


9 3 9